Framingham Heart Study (FHS) 10-Year Cardiovascular Risk Is Associated With Marijuana Use in the Miami Adult Studies on HIV (MASH) Cohort. (7th June 2021) - Rodriguez, Jose Bastida; Hernandez, Jacqueline; Teeman, Colby; Huang, Yongjun; Liu, Qingyun; Martinez, Sabrina; Campa, Adriana; Seminario, Leslie; Jasmin, Jupshy; Tamargo, Javier; Johnson, Angelique; Baum, Marianna
Abstract: Objectives: Illicit drug use can lead to adverse cardiovascular events; it is an additional risk factor for cardiovascular disease. Thus, we sought to determine the association between CVD and drug use in people living with HIV (PLWH) using the FHS 10-year risk. Methods: Participants were selected from the MASH cohort. Demographics, anthropometrics, bioimpedance analysis, and fasting blood samples were collected by trained personnel. HIV Viral Load (VL, copies/ml) was abstracted from medical charts. Urine toxicology was used to determine current illicit drug use. Descriptive statistics were used to analyze demographics, HIV status, and VL (undetectable VL < 50 copies/ml). CVD (10-year risk) score was calculated using a formula based on CVD risk factors. An independent sample t-test was used to compare the mean CVD risk score between drug users and non-users. Linear regression was used to find an association between drug users and CVD 10-year risk while controlling for sex and infection status. Results: Participants' mean age was 54.6 ± 7.9 years ( n  = 1034), 58% male and 63.8% Black. About 46.8% were PLWH and 90.9% had an undetectable VL. The average CVD 10-year risk of all participants was 15.1% and 49.6% of participants used illicit substances. A univariate linear regression showed a positive association between FHS 10-year risk and marijuana use (b = 2.260 SE = 1.036, 95% CI: 0.227–4.293; P  = 0.029). After adjusting for sex and HIV status the association remained significant (b = 2.322 SE = 1.028, 95% CI: 0.304–4.340; P  = 0.024). Comparing the mean 10-year risk between groups, a significant difference between marijuana users and non-users was seen regardless of infection status and age (95% CI: −4.293- −0.227; P  = 0.029). Separating by sex, only males showed a significant difference in 10-year risk when comparing marijuana users to non-users irrespective of infection status and age (95% CI: −6.394- −0.8373; P  = 0.011). No association was determined between 10-year risk and other substances, including cocaine, fentanyl, and amphetamines. Conclusions: Marijuana use seems to be a strong predictor of CVD risk in minority populations. However, other substances of abuse did not exhibit a cardiovascular effect regardless of HIV status or sex. Further studies are needed to examine the relationship between the use of marijuana and CVD. Funding Sources: National Institute on Drug Abuse.